Racial and Ethnic Discrimination in the Labor Market for Child Care Teachers - Casey Boyd-Swan; Chris M. Herbst (Institute of Labor Economics (IZA), 2017)
This paper examines racial and ethnic discrimination in the labor market for center-based child care teachers. We assemble a novel dataset that combines a resume audit study of child care centers in several large U.S. cities with a follow-up survey of the providers in the original audit sample. The provider survey was administered to obtain detailed information about the children, teachers, and administrators within the center. Together, these data provide three insights about the influence of applicant race and ethnicity on teacher hiring. First, we uncover robust evidence of discrimination: black and Hispanic applicants receive significantly fewer interview requests than observationally equivalent whites. Nevertheless, we show that program directors exhibit strong own-race preferences: white directors favor white applicants, while minority directors favor those from their own racial and ethnic background. Second, our results suggest that teacher hiring is consistent with a model of customer discrimination. In particular, the racial and ethnic composition of children attending the center is strongly correlated with the characteristics of job-seekers receiving an interview request. Finally, we show that states' child care regulations and quality certification programs mitigate or eliminate entirely the racial and ethnic gap in interview requests. These benefits accrue disproportionately to high-skilled minorities, and to those applying to child care centers located in high-income communities. We posit that these firm-level licensing requirements increase the cost to employers of using race and ethnicity as signals of teacher productivity.
Keywords: J71; 330; customer discrimination; racial/ethnic labor market discrimination; child care market; child care regulations